Extraction of uncertain parameters of single-diode model of a photovoltaic panel using simulated annealing optimization - Ramzi Ben Messaoud (Energy Reports, 2020)
In this article, our goal is to improve the estimation of the parameters of solar photovoltaic models, we propose a method based on Simulated Annealing (SA) Optimization, the proposed algorithm takes into account the uncertainties of measurements. This algorithm consists of three steps such as the extraction of the parameters in a conventional manner, then the determination of the uncertainties of each parameter, finally the determination of the instantaneous parameters taking into account the results of the first two steps. For the validation of the proposed theoretical developments, the algorithm is applied to four different PV parameter estimation problems. The results obtained are compared with well-established algorithms to confirm its effectiveness. These comparisons have shown that the proposed method exhibits largely effective performances than existing methods in the literature.
Keywords: 330; Parameter estimation; Photovoltaic model; Simulated annealing optimization; Uncertainties measurements